2004
DOI: 10.1200/jco.2004.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Followed by Extrapleural Pneumonectomy in Malignant Pleural Mesothelioma

Abstract: For patients with potentially operable MPM, the availability of active and well-tolerated chemotherapy regimens, the fact that extrapleural pneumonectomy can be safely performed after neoadjuvant chemotherapy in an experienced center, and the promising results regarding survival in our pilot study warrant further investigation of the role of neoadjuvant chemotherapy in a multimodality strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
139
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(146 citation statements)
references
References 32 publications
5
139
0
2
Order By: Relevance
“…18 F-FDG PET/CT would thus be more informative for diagnosis of pleural diseases than examination with 18 F-FDG PET (7). The incidence of malignant pleural mesothelioma (MPM) in many countries including Japan is rising, as predicted (8,9), (10,11). Only a small number of patients with MPM are deemed suitable candidates for multimodality therapy which includes chemotherapy, surgery and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDG PET/CT would thus be more informative for diagnosis of pleural diseases than examination with 18 F-FDG PET (7). The incidence of malignant pleural mesothelioma (MPM) in many countries including Japan is rising, as predicted (8,9), (10,11). Only a small number of patients with MPM are deemed suitable candidates for multimodality therapy which includes chemotherapy, surgery and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is valid for the classic trimodality approach pioneered by Sugarbaker and colleagues [15], for the neoadjuvant chemotherapy strategy proposed by Weder and associates [5], and for the intensitymodulated adjuvant radiotherapy established by Rice and coworkers [16]. Nonetheless, results achieved are not yet satisfying, and median survival is quite low.…”
Section: Commentmentioning
confidence: 74%
“…Despite extensive surgical removal provided by extrapleural pneumonectomy, patients relapsed rapidly. Therefore, most treatment regimens have focused on radiation therapy, chemotherapy and immunotherapy multimodality treatment [4], or neoadjuvant chemotherapy [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, McCormack et al [43] reported an operative mortality of 1.8% for P/D. The response rate of the cisplatin-GEM doublet has been reported to range between 16 and 47%, and was 32% in a neo-adjuvant trial [44]. The response to the pemetrexed-cisplatin doublet has been reported to be 41% in advanced MPM, so most groups are now exploring this combination in a neo-adjuvant setting.…”
Section: Radiotherapy For Malignant Pleural Mesotheliomamentioning
confidence: 99%